Dental plaque formation and salivary mutans streptococci in schoolchildren after use of xylitol-containing chewing gum - PERNILLA LIF HOLGERSON, INGER SJÖSTRÖM, CHRISTINA STECKSÉN-BLICKS, & (IAPD and Blackwell, 2007)
The aim of this study was to investigate the effect of a fixed daily dose of xylitol on mutans streptococci in saliva and the amount of visible dental plaque.